PERSPEKTIF KONSELING PASTORAL DALAM MENGHADAPI BULLYING REMAJA AKHIR USIA 15-18 TAHUN YANG MEMPENGARUHI PSIKOLOGIS - Junardi Saleleubaja; Arianto Zebua; Musliadi Kumar; Fernando Agung Mulia Saragih; Hendina Saragih (Jurnal Pendidikan Agama dan Teologi, 2024)
This article discusses the perspective of pastoral counseling in addressing bullying among late adolescents aged 15-18 years that affects the psychological well-being of adolescents. Bullying is a significant social problem among teenagers and can have negative impacts on their psychological well-being. The purpose of this research is to explore the role of pastoral counseling in helping adolescents cope with the psychological effects resulting from bullying. The research method used in this study is a qualitative descriptive method with a literature review approach, depicting the characteristics of late adolescents aged 15-18 years who are vulnerable to bullying and its impact on their psychological well-being. The research findings indicate that pastoral counseling can provide emotional support, moral guidance, and reinforcement of religious values that assist adolescents in overcoming the pressures of bullying. The implications of this research are that the perspective of pastoral counseling is relevant and beneficial in aiding the protection and recovery of adolescents affected by bullying. It is hoped that this article will provide further understanding of the role of pastoral counseling in addressing bullying among late adolescents aged 15-18 years.